Peran Strategis Guru Pendidikan Agama Islam dalam Memperkuat Kecerdasan Spiritual Siswa Sekolah Menengah Atas - Sari, Zakiyyah Rahma; Rahim, Fathor; Mardiana, Dina (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2025)
Strengthening spiritual intelligence often faces challenges. This study aims to analyze the strategic role of Islamic Religious Education (IRE) teachers in enhancing the spiritual intelligence of high school students. This qualitative research employed a case study design. Data collection was conducted using interviews, observations, and documentation. The results show that IRE teachers have fulfilled their educational role by transferring contextual religious knowledge, exemplifying exemplary attitudes, habituating worship, and providing moral guidance that influences student behavior. As facilitators, IRE teachers play a role in delivering reflective learning spaces, encouraging religious discussions, and applying religious activities. However, obstacles remain, including low family support, declining student motivation to learn, and limited innovation in learning methods and media. This study concludes that strengthening students' spiritual intelligence requires the role of IRE teachers who are innovative, reflective, and collaborative. Synergistic efforts among teachers, schools, and parents are crucial to creating an environment conducive to students' spiritual growth, so that IRE can serve as a vehicle for knowledge transfer, character transformation, and spiritual growth.